Suppression of Vps13 adaptor protein mutants reveals a central role for PI4P in regulating prospore membrane extension. - Tsuyoshi S Nakamura (Public Library of Science (PLoS), 2021)
Vps13 family proteins are proposed to function in bulk lipid transfer between membranes, but little is known about their regulation. During sporulation of Saccharomyces cerevisiae, Vps13 localizes to the prospore membrane (PSM) via the Spo71-Spo73 adaptor complex. We previously reported that loss of any of these proteins causes PSM extension and subsequent sporulation defects, yet their precise function remains unclear. Here, we performed a genetic screen and identified genes coding for a fragment of phosphatidylinositol (PI) 4-kinase catalytic subunit and PI 4-kinase noncatalytic subunit as multicopy suppressors of spo73Δ. Further genetic and cytological analyses revealed that lowering PI4P levels in the PSM rescues the spo73Δ defects. Furthermore, overexpression of VPS13 and lowering PI4P levels synergistically rescued the defect of a spo71Δ spo73Δ double mutant, suggesting that PI4P might regulate Vps13 function. In addition, we show that an N-terminal fragment of Vps13 has affinity for the endoplasmic reticulum (ER), and ER-plasma membrane (PM) tethers localize along the PSM in a manner dependent on Vps13 and the adaptor complex. These observations suggest that Vps13 and the adaptor complex recruit ER-PM tethers to ER-PSM contact sites. Our analysis revealed that involvement of a phosphoinositide, PI4P, in regulation of Vps13, and also suggest that distinct contact site proteins function cooperatively to promote de novo membrane formation.